Clinicians in the Veterans Health Administration initiate gender-affirming hormone therapy in concordance with clinical guideline recommendations - Jasuja, Guneet K.; Wolfe, Hill L.; Reisman, Joel I.; Vimalananda, Varsha G.; Rao, Sowmya R.; Blosnich, John R.; Livingston, Nicholas A.; Shipherd, Jillian C. (Frontiers in Endocrinology, 2024)
Background: Gender-affirming hormone therapy (GAHT) is a common medical intervention sought by transgender and gender diverse (TGD) individuals. Initiating GAHT in accordance with clinical guideline recommendations ensures delivery of high-quality care. However, no prior studies have examined how current GAHT initiation compares to recommended GAHT initiation.Objective: This study assessed guideline concordance around feminizing and masculinizing GAHT initiation in the Veterans Health Administration (VHA).The sample included 4,676 veterans with a gender identity disorder diagnosis who initiated feminizing (n=3,547) and masculinizing (n=1,129) GAHT between 2007 and 2018 in VHA. Demographics and health conditions on veterans receiving feminizing and masculinizing GAHT were assessed. Proportion of guideline concordant veterans on six VHA guidelines on feminizing and masculinizing GAHT initiation were determined.Results: Compared to veterans receiving masculinizing GAHT, a higher proportion of veterans receiving feminizing GAHT were older (≥60 years: 23.7% vs. 6.3%), White non-Hispanic (83.5% vs. 57.6%), and had a higher number of comorbidities (≥7: 14.0% vs. 10.6%). A higher proportion of veterans receiving masculinizing GAHT were Black non-Hispanic (21.5% vs.3.5%), had posttraumatic stress disorder (43.0% vs. 33.9%) and positive military sexual trauma (33.5% vs.16.8%; all p-values<0.001) than veterans receiving feminizing GAHT. Among veterans who started feminizing GAHT with estrogen, 97.0% were guideline concordant due to no documentation of venous thromboembolism, breast cancer, stroke, or myocardial infarction.Among veterans who started spironolactone as part of feminizing GAHT, 98.1% were guideline concordant as they had no documentation of hyperkalemia or acute renal failure. Among veterans starting masculinizing GAHT, 90.1% were guideline concordant due to no documentation of contraindications, such as breast or prostate cancer. Hematocrit had been measured in 91.8% of veterans before initiating masculinizing GAHT, with 96.5% not having an elevated hematocrit (<50%) prior to starting masculinizing GAHT. Among veterans initiating feminizing and masculinizing GAHT, 91.2% had documentation of a gender identity disorder diagnosis prior to GAHT initiation.We observed high concordance between current GAHT initiation practices in VHA and guidelines, particularly for feminizing GAHT. Findings suggest that VHA clinicians are initiating feminizing GAHT in concordance with clinical guidelines. Future work should assess guideline concordance on monitoring and management of GAHT in VHA.